Social and cultural discourses that shape male youths' masculinity and conceptions of risk and vulnerability to HIV and AIDS in Rundu Urban Constituency, Kavango region, Namibia,Social and cultural practices that shape male youths' masculinity and conceptions of risk and vulnerability to HIV and AIDS in Rundu Urban Conservancy, Kavango region, Namibia - Shikukutu, Faustinus (Rhodes University, Faculty of Education, Department of Education, 2013)
HIV and AIDS still challenges the best efforts of public health and medical establishments and continues to ravage communities around the world. While measures have been put in place to preclude it from further spread, recent studies in the field of HIV and AIDS prevention intimate that for more efficacious intervention to be realized, it is critical to understand and address the social and cultural practices which influence sexual behavior, particularly understanding how issues of masculinity plays a role in the perpetuation of these behavior. Relying on Bourdieu's theory of social practice, this study explores the inherent enduring nature of habitus and its role in the production and maintenance of masculine and sexual identities that predispose young men to HIV and AIDS. The study was conducted in Rundu Urban Constituency in Kavango Region of Namibia to gain insight into male youth's masculinity and conceptions of risk and vulnerability to HIV and AIDS. The study design was qualitative and interpretive in nature. Data collection strategies included focus group discussions and individual interviews. Twelve male youth aged 17-20 years in two secondary schools (six in each) were selected to participate in the study. Four focus group discussions and fourteen individual interviews were conducted. Institutional ethical clearance from both regional education office and the schools were obtained before undertaking the study. Participants also signed written consent forms before interviews started. The findings of this study revealed that young men from this community were under constant pressure to conform to dominant masculine norms and values. Key in the case of youth in the study was the need to procreate as a dominant marker of one's masculine and sexual identity because it represented a primary source of a 'real' man's social identity in this community. This masculine and sexual identity seemed in itself to be constructed along paternal lines and cultural beliefs, which youth preserved by not only complying, but also reproducing. The sexual activities they reported that would secure their position as `real` men were often those that put them at risk and made them vulnerable to the epidemic.
Keywords: AIDS (Disease) -- Social aspects -- Namibia -- Kavango; AIDS (Disease) in adolescence -- Namibia -- Kavango; HIV (Viruses) -- Social aspects -- Namibia -- Kavango; HIV infections -- Risk factors -- Namibia -- Kavango; Men -- Sexual behavior -- Namibia -- Kavango; Gender identity -- Namibia